The issue of worldview in ecological education - Czartoszewski, Jacek W. (Studia Ecologiae et Bioethicae, 2003)
The XXI century for humanity is a challenge in awareness of failures in the condition of the social environment as well in huge contamination of nature. This problem can be resolved only on the way of grasping the junctures of man in the world toward Absolute and the other adventitious entities. There is a necessary general change of human awareness, which will strengthen love to the other people and amends an evil site between mankind. It should be joined with changing mentality reducing consumption material goods (savings in using up energies and industrial goods) and taking care of remaining for succeeding generations natural environments in better condition than that nowadays. It also needs to create a new high level of outlook upon ecology, which accepts ecological values. This outlook eschewing idealism and inaccuracies should be based on the real ground of Aristotelic and Thomistic orientation. Moreover, it must avoid hatchway in the knowledge, from here society aside from knowledge natures, technical, juridical and economical should own knowing humanistic, which regards anthropology, axioms, theology, and religion (get into completely mode with helping of recognition common sense, wisdom, scientific, philosophic and religionist). On the other way hatchways, inaccuracies, and even contrarieties into understanding the world will become dominant and lead to quarrels and antagonisms. From here floats a huge challenge for leaders, who should take on their own shoulder responsibility upon the future of our planet and humanity.